2021
DOI: 10.3389/fpsyg.2021.803359
|View full text |Cite
|
Sign up to set email alerts
|

“Desire Is Like a Dreadful Monster”: Analysis of Extended Metaphors in L2 Argumentative Essays by Chinese Learners of English

Abstract: This article explores the use, function, and understanding of extended metaphors in L2 argumentative essays by Chinese learners of English. The analysis starts with the identification of linguistic metaphors and extended metaphors in 72 argumentative texts produced by 37 intermediate Chinese English majors. The function of extended metaphors is then analyzed by adopting the bottom-up approach of establishing systematic metaphors from those identified extended metaphors, to draw learners’ communicative intentio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…For native English speakers, 19 speech drafts with an average of 1046 words were gathered on TED talk, a platform dedicated to sharing ideas and knowledge through presentations. The data size was in line with previous research, which was suitable to establish the validity of this study [5,16].…”
Section: Data Collectionsupporting
confidence: 72%
See 2 more Smart Citations
“…For native English speakers, 19 speech drafts with an average of 1046 words were gathered on TED talk, a platform dedicated to sharing ideas and knowledge through presentations. The data size was in line with previous research, which was suitable to establish the validity of this study [5,16].…”
Section: Data Collectionsupporting
confidence: 72%
“…The first strand of studies concerned the patterns and functions of L2 metaphors produced by L2 learners. For example, Lu's study identified extended metaphors and established 11 systematic metaphors (e.g., SPENDING IS A VEHICLE, LOVE IS ILLNESS) in L2 argumentative essays produced by 37 intermediate Chinese English majors, which revealed that these students were able to use metaphors strategically to achieve vividness, coherence, and persuasiveness [5]. Through analyzing metaphor's type frequency and source domains in medical academic papers written by native and non-native speakers of English, a quantitative study found that indirect metaphors had the highest occurrence number, and "object" metaphor and "social actions" metaphor were more frequently applied by native speakers [6].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context the present paper takes the EFL teacher's perspective in implementing a special approach designed to teach metaphor use in discourse and explores its effect on L2 learner texts as the course of study progresses. The texts under study belong to the descriptive-narrative genre, which has not been examined in terms of learners' productive metaphoric competence as much as the argumentative genre (e.g., Nacey 2013;Lu 2021).…”
Section: Introductionmentioning
confidence: 99%
“…However, in recent decades, there has been less discussion about the feasibility and impact of a pedagogical intervention on the development of metaphorical competence. The investigation adds to the understanding of the L2 learners' metaphorical competence by improving instructors' metaphor knowledge and increasing metaphor awareness in L2 writing, teaching, and learning (Lu, 2021 ). The previous study explored hemispheric differences in the processing of metaphors by introducing scientific metaphors as new metaphors and providing orientation mapping from the particular and known domains to the abstract and unfamiliar domains (Huang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%